Incidence and risk factors of chronic daily headache in young adolescents: a school cohort study - Lu, Shiang-Ru; Fuh, Jong-Ling; Wang, Shuu-Jiun; Juang, Kai-Dih; Chen, Shih-Pin; Liao, Yi-Chu; Wang, Yen-Feng (Pediatrics (Evanston), 2013)
This study investigated the incidence and risk factors of chronic daily headache (CDH) and its major subtypes in young adolescents. A field cohort of 3342 adolescents aged 13 to 14 was established in 3 middle schools in Taitung, Taiwan, from 2005 to 2007. Participants without CDH at baseline were annually followed up for 1 to 2 years using the same questionnaires, including the Adolescent Depression Inventory and Pediatric Migraine Disability Assessment. The neurologists made the headache diagnoses based on clinical interviews and headache diaries. The person-time incidence rates and risk factors of incident CDH and its subtypes (ie, chronic migraine [CM] and chronic tension-type headache [CTTH]) were calculated by using Cox proportional hazards models. The cohort completed 5586 person-years (PYs) of follow-up. Sixty-three subjects (21 boys/42 girls) developed incident CDH with an incidence rate of 1.13 per 100 PYs, including 37 with CM (0.66 per 100 PYs) and 22 with CTTH (0.39 per 100 PYs). Thirty-three subjects (52%) had a baseline diagnosis of migraine. The independent risk factors for incident CDH included female gender, acute family financial distress, obesity, higher headache frequency, and a baseline diagnosis of migraine. A higher headache frequency was the only identical risk factor for CDH, CM, and CTTH. A baseline diagnosis of migraine and obesity were significant predictors for both CM and CDH. Female gender was a significant predictor for both CTTH and CDH. Incident CDH was common in young adolescents. Some risk factors for incident CM and CTTH were different.